2021
DOI: 10.1016/j.resuscitation.2021.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation is associated with poor outcome after out-of-hospital cardiac arrest

Abstract: Background: Cardiopulmonary resuscitation after cardiac arrest initiates a whole-body ischemia-reperfusion injury, which may activate the innate immune system, including the complement system. We hypothesized that complement activation and subsequent release of soluble endothelial activation markers were associated with cerebral outcome including death.Methods: Outcome was assessed at six months and defined by cerebral performance category scale (1À2; good outcome, 3À5; poor outcome including death) in 232 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…Our findings showed that the above four complement components were all significantly increased in patients after ROSC compared to healthy volunteers. These findings indicated that these three complement pathways were all activated in patients after ROSC, which is in accordance with a recent study [ 7 ]. After complement activation, C3a and C5a, as pro-inflammatory mediators, can contribute to inflammatory cascade, as evidenced by the elevated serum levels of IL-6 and TNF-α after ROSC in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that the above four complement components were all significantly increased in patients after ROSC compared to healthy volunteers. These findings indicated that these three complement pathways were all activated in patients after ROSC, which is in accordance with a recent study [ 7 ]. After complement activation, C3a and C5a, as pro-inflammatory mediators, can contribute to inflammatory cascade, as evidenced by the elevated serum levels of IL-6 and TNF-α after ROSC in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the cytolytic sC5b-9, as the common end-product of the classical, lectin, and alternative complement pathways, can directly damage cell membrane. Therefore, the elevated serum complement activation products, including C3a, C5a, and sC5b-9, have been reported to be associated with post-cardiac arrest immunoinflammatory response and poor prognosis [ 7 , 11 , 29 ], which is consistent with our result that the non-survivors had higher concentrations of serum C3a, C5a and sC5b-9 than the survivors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Different animal studies have shown the involvement of the complement system in IRI (137). Deposition of the complement components C3d and C5b-9 was seen in reperfused hearts of myocardial infarction patients (138) and associated with an increase in shedding of syndecan-1, a core protein of the endothelial glycocalyx (139,140). Complement inhibition, by administration of a membrane-targeted molecule derived from complement receptor 1 (141) or by administration of dextran sulfate, was shown to be beneficial in experimental myocardial infarction as well as in cardiac transplantation (142).…”
Section: Shedding Of Endothelial Glycocalyx During Ischemia/reperfusi...mentioning
confidence: 99%
“…Postcardiac arrest syndrome (PCAS) is characterized by reperfusion injury from systemic ischemia, myocardial dysfunction, brain, and other vital organ injury, superimposed on underlying diseases, all of which explain the low survival rate of hospital discharge. After CA, a systemic inflammatory response occurs that has been shown to occur in the reperfusion stage, with the release of pro-inflammatory cytokines by leukocytes and endothelial cells through the activation of leukocytes and endothelial cells and the release of secondary cytokines [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. EC expresses a wide spectrum of cytokines and chemokines, including pro-inflammatory interleukins; IL-1β, IL-3, IL-5, IL-6, IL-8, IL-11, IL-15, and tumor necrosis factor (TNF-α), as well as anti-inflammatory cytokines such as IL-1 receptor antagonist (IL-1ra), IL-10, IL-13, and transforming growth factor beta (TGF-β) [ 61 , 62 , 63 ].…”
Section: Models Of Endothelial Activationmentioning
confidence: 99%